Robust Control of a Brushless Servo Motor Using Sliding Mode - Radita Arindya (Institute of Advanced Engineering and Science, 2012)
The application of sliding mode techniques the position control of a brushless servo motor is discussed. Such control laws are well suited for electric power inverter. However, high frequency commutations are avoided due to the mechanical systems. Various recent schemes are studied and operated to derive control solutions which are technically feasible. In spite of straightforward applications the resulting systems show robust performances to parametric variations and disturbances. Robustness studied with respect to rotor flux uncertainties and to stator resistance which varies with the temperature of the motor.